Oral habits management in pediatric dentistry review of the literature - Awuapara Flores, Shereen (2022)
Oral habits are responsible for many dentoalveolar and soft tissue disorders. Knowledge of the management of these is of vital importance for the clinician. The purpose of this review is to search in the scientific literature, the management of the most common oral habits, in order to create a treatment guide that helps the clinician in their management. Methods: 121 articles were revised from the databases Pubmed, Cochrane library, Ebsco, Scielo and Google Scholar. Systematic reviews, meta analysis, randomized clinical trials and clinical guides were prioritized in the search, with a publish date not greater than 5 years. After the final review and selection, 45 articles were used. The search was carried out in English and Spanish, using the keywords for the topics: non-nutritive sucking, atypical swallowing, mouth breathing, bruxism, and lip sucking or biting. Conclusions: the management of oral habits is multidisciplinary. There are different types of therapies and appliances for each of them, so it is important to make an adequate diagnosis and treatment plan according to the conditions and particular needs of each patient.